Technocultural and Multicriteria Analysis of Wastewater Management in Cirebon's Batik Industry - Nazuwatussya’diyah Nazuwatussya’diyah; Estiyanti Ekawati; Ashari Budi Nugraha; Elfi Yulia; Eggie Rizki Srie Rejeki (Jurnal Sosioteknologi, 2026)
Batik Wastewater Management in Cirebon continues to face persistent implementation challenges, despite the availability of treatment technologies. This condition reflects a technocultural misalignment between technological solutions and community capacity. Therefore, this study examines wastewater management in Cirebon's batik industry using a dual Analytical Hierarchy Process (AHP) framework that integrates environmental, technological, and social dimensions. Of the environmental dimension, laboratory analysis of eight wastewater samples revealed that 9 of 14 parameters exceeded Indonesian regulatory standards, with oil & grease levels exceeding the permissible limit by over 1,000-fold. The associate data-driven AHP prioritization identified oil and grease, BOD, and COD as the highest-priority parameters. Of the technological and social dimensions, the field survey documented the systemic discontinuation of treatment practices following the cessation of external support, attributable to technocultural barriers. The associate AHP evaluation of six treatment strategies across environmental (36%), technological (41%), and social (23%) criteria revealed the environmental-social paradox: integrated multi-stage WWTP ranked third (11.7%), due to prohibitive costs and operational complexity, while neutralization (28%) and equalization & settling (26%) ranked first and second, respectively. The convergence of oil and grease as the highest environmental priority and wax recovery as the most implementable strategy identifies a major entry point that simultaneously satisfies the three criteria. It serves as the foundation of a graduated three-phase implementation strategy. This study contributes methodologically through dual data-driven AHP to produce objective prioritization; theoretically through reframing pollution control as a techno cultural challenge; and practically through a graduated implementation strategy based on social capacity.